2014
DOI: 10.3389/fpsyg.2014.01013
|View full text |Cite
|
Sign up to set email alerts
|

Insular activation during reward anticipation reflects duration of illness in abstinent pathological gamblers

Abstract: Pathological gambling (PG) is a chronic mental disorder characterized by a difficulty restraining gambling behavior despite negative consequences. Although brain abnormalities in patients with substance use disorders are caused by repetitive drug use and recover partly with drug abstinence, the relationship between brain activity and duration of illness or abstinence of gambling behavior in PG patients remains unclear. Here, using functional magnetic resonance imaging, we compared the brain activity of 23 PG p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 61 publications
1
18
0
Order By: Relevance
“…Rauscent et al 2016). Insular activation during reward anticipation reflects the duration of illness in abstinent pathological gamblers (Tsurumi et al 2014). The increased functional connection between the left frontoparietal network and anterior insula predicts steeper devaluation of delayed rewards in smokers (Clewett et al 2014).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Rauscent et al 2016). Insular activation during reward anticipation reflects the duration of illness in abstinent pathological gamblers (Tsurumi et al 2014). The increased functional connection between the left frontoparietal network and anterior insula predicts steeper devaluation of delayed rewards in smokers (Clewett et al 2014).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…For example, Janes et al 126 demonstrated that increased anterior insular cortex activation to smoking cues predicted slips among abstinent nicotine addicts, while Claus et al 127 showed that increased insular activation was associated with addiction severity in alcohol addiction. Furthermore, Tsurumi et al 128 found that insular activation in a reward anticipation task was inversely related to the duration of illness among abstinent pathological gamblers. While this finding seems somewhat at odds with the finding reported earlier, 112 we suggest that this discrepancy may be due to the nature of the task.…”
Section: Neurophysiological Abnormalities In Addictionmentioning
confidence: 99%
“…While this finding seems somewhat at odds with the finding reported earlier, 112 we suggest that this discrepancy may be due to the nature of the task. Tsurumi et al 128 used points instead of money as the incentive and, thus, the decrease in activation may due to the specificity in the reward responses mentioned earlier. 116 …”
Section: Neurophysiological Abnormalities In Addictionmentioning
confidence: 99%
“…During reward outcome, gambling disorder patients showed increased activation in the posterior orbitofrontal cortex to monetary gain outcome compared with controls. In a modified version of the monetary incentive delay task (points instead of money to express the amount of reward) [ 66 •], gambling disorder patients did not differ from controls in striatal activation during reward anticipation but displayed reduced activation in the insula, which was negatively related to the duration of the illness, suggesting that this alteration may result from excessive gambling.…”
Section: Gain Processingmentioning
confidence: 99%